Dryad data on field study - Piper, Frida I; Gundale, Michael; Fuenzalida, Tomás; Fajardo, Alex (Dryad Digital Repository, 2019)
Leaf traits (N, P, NSC, polyphenols, C/N and humidity), field herbivory, and relative consumption rate by Ormiscodes amphimone in non choice experiments of Nothofagus pumilio, N. antarctica and N. betuloides in Patagonia; relative consumption rate by Ormiscodes amphimone in non choice experiments with foliage of N. pumilio and N. antarctica from stands with and without ongoing outbreaks.